1985
DOI: 10.1002/1097-4679(198505)41:3<299::aid-jclp2270410302>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment characteristics of psychiatric programs that correlate with patient community adjustment

Abstract: This large Veterans Administration cooperative study sought to identify the ward milieu characteristics of effective psychiatric programs. It was developed as a multivariable, correlational study that involved systematic observations of program characteristics and outcome effectiveness of wards as they operated in their usual manner. Seventy‐nine wards in 18 hospitals provided 11,283 patients eligible for follow‐up. Eleven treatment characteristics were found to be correlated to patients' community adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…There is some evidence that wards with more social interaction are associated with better clinical outcome (Collins et al, 1985). However, owing to staff ratios of typically one nurse to four or five patients and the numerous other demands on nurses' time, one-toone interactions with staff form a small part of each patient's day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that wards with more social interaction are associated with better clinical outcome (Collins et al, 1985). However, owing to staff ratios of typically one nurse to four or five patients and the numerous other demands on nurses' time, one-toone interactions with staff form a small part of each patient's day.…”
Section: Discussionmentioning
confidence: 99%
“…Arguably it is the quality of relationships that matters to patients, and a small number of highly significant interactions may be more important than the amount of time spent interacting. However, wards with more active patients seem to be associated with better therapeutic outcome (Collins et al, 1985) and numerous reports, including that from the Department of Health (2002), cite the advantages of organised activities and the deleterious impact of inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that social climate may be a potential contributor to treatment outcome (Collins et al, 1985;Ellsworth, 1983;Gunderson, 1983;Hansen & Slevin, 1996;Melle et al, 1996). However, one study failed to find such a link and suggested that a therapeutic social climate was associated with a longer length of hospital stay (Lehman et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Although much has changed in the nature of inpatient provision with the move away from the hospital asylum, the essential association between social interaction and better clinical outcome continued to be reported across the next two decades [3] as has the low level of patient and staff interaction [4]. It seems likely that although no recent study has examined the issue, these associations remain.…”
Section: Introductionmentioning
confidence: 99%